Stone heart - Rice, Luanne (Bantam Books, 2005)
When Maria Dark returns to Connecticut after years of traveling as an archaeologist, she learns that her sister's once-idyllic marriage is now permeated with a dangerously perverse obsession, in a powerful novel of family bonds and home.